Supervision of an Industrial Process of Milk Production using Fuzzy Logic - Zermane Hanane (Proceedings of the International Conference on Industrial Engineering and Operations Management Paris, France, 2018)
Proceedings of the International Conference on Industrial Engineering and Operations Management Paris, France, July 26-27, 2018 Supervision of an Industrial Process of Milk Production using Fuzzy Logic Hanane Zermane, Samira Brahmi, Naima Zerari, Rachad Kasmi Laboratory of Automation and Manufacturing, Industrial Engineering Department University Batna 2, Batna, Algeria hananezermane@yahoo.fr, brahmi.samira@gmail.com, n.zerari@yahoo.fr, kasmiradwan08@gmail.comAbstract Because we usually deal with real - world systems with real - world constraints (cost, computer resources, size, weight, power, heat dissipation, etc.), it is understood that the simplest method to accomplish a task is the one that should be used. Experts usually rely on common sense when they solve problems. They also use vague and ambiguous terms. Other experts have no difficulties with understanding and interpreting this statement because they have the background to hearing problems described like this. However, a knowledge engineer would have difficulties providing a computer with the same level of understanding. In a complex industrial process, how can we represent expert knowledge that uses vague and fuzzy terms in a computer to control it? In this work, the application is developed to control the pretreatment and pasteurization station of milk localized in Batna (Algeria) by adopting a control approach based on expert knowledge and fuzzy logic